2012
DOI: 10.1371/journal.pone.0047465
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin I Regulates Patterned Spontaneous Activity in the Developing Rat Retina via Calcium Binding to the C2AB Domains

Abstract: BackgroundIn neonatal binocular animals, the developing retina displays patterned spontaneous activity termed retinal waves, which are initiated by a single class of interneurons (starburst amacrine cells, SACs) that release neurotransmitters. Although SACs are shown to regulate wave dynamics, little is known regarding how altering the proteins involved in neurotransmitter release may affect wave dynamics. Synaptotagmin (Syt) family harbors two Ca2+-binding domains (C2A and C2B) which serve as Ca2+ sensors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…To examine whether knockdown of A 2A R alters the wave pattern, we measured the duration and amplitude of individual Ca 2+ transients, using the criteria set by a program developed in our previous study [28]. We found that knockdown of A 2A R did not significantly change the duration or amplitude of Ca 2+ transients compared to the control (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…To examine whether knockdown of A 2A R alters the wave pattern, we measured the duration and amplitude of individual Ca 2+ transients, using the criteria set by a program developed in our previous study [28]. We found that knockdown of A 2A R did not significantly change the duration or amplitude of Ca 2+ transients compared to the control (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Our previous study has also shown that the mGluR2 promoter can drive SAC-specific expression in retinal explants with ∼84% of the cells targeted to SACs compared to 8% targeted to SACs with the CMV promoter [28]. Moreover, using a horizontal electroporation configuration, gene expression driven by the mGluR2 promoter can achieve high transfection efficiency (∼50%) that is sufficient to modulate the molecular machinery in SACs and further alters the dynamics of retinal waves [28]. Hence, in the following experiments, we utilized the mGluR2 promoter to target expression of A 2A R or its mutant to SACs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, some inhibitory neurons in hippocampal slice culture and excitatory autaptic neurons in dissociated culture are less affected by syt1 deficiency , suggesting that syt1 is not the primary calcium sensor for all synchronous release even within the same brain region. Many studies have been performed to determine how the C2A and C2B domains of syt1 bind calcium and differentially modulate synchronous, asynchronous and spontaneous release , but there is an emerging consensus around the notion that these domains cooperate to promote synchronous fusion and clamp delayed fusion . Overall, these studies suggest that vesicles containing syt1 are likely to be trafficked to the plasma membrane for synchronous evoked release.…”
Section: Vesicle‐associated Proteins That Segregate Vesicle Poolsmentioning
confidence: 99%
“…Once Ca 2+ ions bind to Ca 2+ sensors such as synaptotagmin I (Syt I) (6), the vesicle membrane fuses with the SAC plasma membrane, allowing neurotransmitters to be released and received by neighboring SACs and RGCs. Our previous study showed that the frequency of cholinergic waves is dampened by weakening Ca 2+ binding to the C2A/B domain of Syt I in SACs (7), suggesting that a key change in the release machinery of SACs is sufficient to alter the temporal patterns of stage II retinal waves. In addition to Syt I, the essential fusion machinery during exocytosis is the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex, consisting of a vesicle membrane Significance Patterned spontaneous activity can modify the structure and function of neural circuits during development, such as retinal waves essential for establishing functional visual circuits.…”
mentioning
confidence: 98%